2022
DOI: 10.1155/2022/5677655
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Surround Suppression Effect on the Contrast Sensitivity of V1 Neurons in Cats

Abstract: Surround suppression (SS) is a phenomenon that a neuron’s response to visual stimuli within the classical receptive field (cRF) is suppressed by a concurrent stimulation in the surrounding receptive field (sRF) beyond the cRF. Studies show that SS affects neuronal response contrast sensitivity in the primary visual cortex (V1). However, the underlying mechanisms remain unclear. Here, we examined SS effect on the contrast sensitivity of cats’ V1 neurons with different preferred SFs using external noise-masked v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 111 publications
(209 reference statements)
0
2
0
Order By: Relevance
“…This work addresses the surrounding suppression, that is, size modulation of firing rate and gamma oscillation properties, where stimulus size is the only variable and long‐range horizontal connection is the only influencing factor. On this basis, this topic can also be expanded in the following directions: Other manifestations of surround suppression can be considered, such as reduced contrast sensitivity in V1 neurons (Yu et al, 2022); different stimulus properties inside and outside the receptive field can be considered, for example, increased firing rates of central neurons when orthogonal stimuli are presented in the surroundings (Cavanaugh et al, 2002; Keller et al, 2020); additional visual stimulus properties can be considered, such as surround suppression of firing rate that occurs only at strong centre contrasts, or even a boost to small centre contrasts (Rubin et al, 2015; Schwabe et al, 2010); other types of long‐range connections can be considered, because it has been experimentally demonstrated that mammalian visual cortex contains long‐range inhibitory connections, but the exact spatial distribution and function are unclear (Chen et al, 2005; McDonald & Burkhalter, 1993); delving deeper into some of the mathematical properties of the model, for example, Jadi and Sejnowski (2014) found that the shape of the neuron response function in the induction‐stabilized network has an important influence on the modulation of the gamma oscillation properties, similarly, Rubin et al (2015) emphasized the importance of the supralinear output–input function of neurons for surround suppression.…”
Section: Discussionmentioning
confidence: 99%
“…This work addresses the surrounding suppression, that is, size modulation of firing rate and gamma oscillation properties, where stimulus size is the only variable and long‐range horizontal connection is the only influencing factor. On this basis, this topic can also be expanded in the following directions: Other manifestations of surround suppression can be considered, such as reduced contrast sensitivity in V1 neurons (Yu et al, 2022); different stimulus properties inside and outside the receptive field can be considered, for example, increased firing rates of central neurons when orthogonal stimuli are presented in the surroundings (Cavanaugh et al, 2002; Keller et al, 2020); additional visual stimulus properties can be considered, such as surround suppression of firing rate that occurs only at strong centre contrasts, or even a boost to small centre contrasts (Rubin et al, 2015; Schwabe et al, 2010); other types of long‐range connections can be considered, because it has been experimentally demonstrated that mammalian visual cortex contains long‐range inhibitory connections, but the exact spatial distribution and function are unclear (Chen et al, 2005; McDonald & Burkhalter, 1993); delving deeper into some of the mathematical properties of the model, for example, Jadi and Sejnowski (2014) found that the shape of the neuron response function in the induction‐stabilized network has an important influence on the modulation of the gamma oscillation properties, similarly, Rubin et al (2015) emphasized the importance of the supralinear output–input function of neurons for surround suppression.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies (Alitto et al, 2019;Cavanaugh et al, 2002;DeAngelis et al, 1994;Fisher et al, 2017;Keller et al, 2020a;Levitt and Lund, 2002;Vangeneugden et al, 2019;Yu et al, 2022) have used 1D models (DoG or RoG) to describe the SS in patch-size tuning, but a 2D model (Roberts et al, 2005;Sceniak et al, 2006) is more appropriate to describe the properties of spatial integration because the cortical neuron at a given V1 depth and visual stimuli used in visual space are both in 2D space. Our study also provides evaluations for different CN models in 2D space (in the STAR Methods section).…”
Section: Descriptive Models For V1 Spatial Integrationmentioning
confidence: 99%